Statistical thermodynamics of the substitutional short-range atomic order and kinematics of the diffuse scattering of radiations in (para)magnetic F.C.C.-Ni-Fe alloys - Bokoch, S.M.; Tatarenko, V.A.; Vernyhora, I.V. (Успехи физики металлов, 2012)
In imitation of f.c.c.-Ni—Fe alloy, the statistical-thermodynamic approach is applied for quantitative analysis of the thermal and composition—magnetic moment fluctuations’ influence on the kinematic diffuse-scattering intensity of radiations (X-rays or thermal neutrons) in magnetic alloys with the atomic short-range order (SRO). На прикладі стопу ГЦК-Ni—Fe застосовано статистично-термодинамічний підхід до чисельної аналізи впливу термічних і концентраційно-магнетних флюктуацій на інтенсивність кінематичного дифузного розсіяння випромінення (Рентґенових променів або теплових невтронів) у атомарно невпорядкованих (з близьким порядком (БП)) магнетних стопах. На примере сплава ГЦК-Ni—Fe применён статистико-термодинамический подход к численному анализу влияния термических и концентрационно-магнитных флюктуаций на интенсивность кинематического диффузного рассеяния излучений (рентгеновских лучей или тепловых нейтронов) в атомно неупорядоченных (с ближним порядком (БП)) магнитных сплавах.